Peran Pendidikan Terhadap Tingkat Kesulitan Mencari Pekerjaan (Studi Kasus Kelurahan Tuatunu Indah Kota Pangkalpinang) - Kurniawan, Rian; Azekawati Juningsih, Dessy; Jessyca (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
The relationship between education and the economy has always been an important issue. Education is one of the things whose existence is considered very important for human life. The existence of education can also help boost the economy of citizens. Education is not only in the form of formal education, but there is also an increase in creativity that can help a person find a job according to their interests and talents. Education is also considered one of the means to build a superior civilization. Education can increase community participation in social and economic activities. This study aims to determine the role of education in the economy. This research focuses on the field of education as well as the economy of the Tuatunu Indah Village community. Thus the relationship between education and the economy can be concluded.